Survey on Knowledge, Attitudes, and Training Needs of Italian Residents on Genetic Tests for Hereditary Breast and Colorectal Cancer. (23rd June 2014) - Panic, Nikola; Leoncini, Emanuele; Di Giannantonio, Paolo; Simone, Benedetto; Silenzi, Andrea; Ferriero, Anna Maria; Falvo, Roberto; Silvestrini, Giulia; Cadeddu, Chiara; Marzuillo, Carolina; De Vito, Corrado; Ricciardi, Walter; et al.
Abstract : Objectives. The aim of the study was to assess knowledge and attitudes of medical residents working in Università Cattolica del Sacro Cuore, Rome, Italy, on genetic tests for breast and colorectal cancer. Methods. We distributed self-administered questionnaire to the residents. Logistic regression models were used to evaluate the determinants of knowledge and attitudes towards the tests. Results. Of 754 residents, 364 filled in questionnaire. Around 70% and 20% answered correctly >80% of questions on breast and colorectal cancer tests, respectively. Knowledge on tests for breast cancer was higher among residents who attended course on cancer genetic testing during graduate training (odds ratio (OR): 1.72; 95% confidence interval (CI): 1.05–2.82) and inversely associated with male gender (OR: 0.55; 95% CI: 0.35–0.87). As for colorectal cancer, residents were more knowledgeable if they attended courses on cancer genetic testing (OR: 2.08; 95% CI: 1.07–4.03) or postgraduate training courses in epidemiology and evidence-based medicine (OR: 1.95; 95% CI: 1.03–3.69). More than 70% asked for the additional training on the genetic tests for cancer during the specialization school. Conclusion. The knowledge of Italian residents on genetic tests for colorectal cancer appears to be insufficient. There is a need for additional training in this field.